Development of “Alat Bantu Pengambilan Keputusan ber-KB” Application - Erni Dwi Widyana; Ari Kusmiwiyati (EMBRIO: Jurnal Kebidanan, 2022)
Women of childbearing age are very vulnerable to having difficulty in determining a proper contraceptive method due to poor knowledge about the safety of these contraceptive methods. Counseling with Decision-Making Aids is an important thing in the provision of family planning services. WHO has developed Decision-Making Tool as a manual family planning decision aid which was adapted by BKKBN and STARH as “Alat Bantu Pengambilan Keputusan ber-KB”. Such tool is made in the form of a booklet with two sides which is still rarely used by midwives when conducting family planning counseling. This study aims to analyze the results of trial on application-based "ABPK" product. This was a study with the Research and Development method. The study population was all midwives who provided family planning services as many as 10 people and Women of Childbearing Age who visited Sukorejo Community Health Center, Pasuruan for family planning service in August–October 2020 as many as 40 people. The samples involved Women of Childbearing Age who met the inclusion criteria selected with total sampling. The study instrument used here was a questionnaire. Data were analyzed using qualitative descriptive analysis technique. The results of the study showed that the developed "ABPK ber-KB" application was considered good and feasible to be used as a counseling media with a value of 86%. In addition, this android-based application medium was relatively easy to use, more interesting, and informative.